Factors associated with knowledge on self-administration of eye drop instillation among Glaucoma patients attending Eye clinic, Teaching Hospital Jaffna - Ameliya Rachel, J.A.; Meera, S.; Jegapragash, V.; Malaravan, M. (University of Jaffna, 2024)
At least 2.2 billion individuals suffer from glaucoma, which is an asymptomatic chronic eye illness leading to complete blindness. Increased intraocular pressure is a clinical contributor to glaucoma; thus, to reduce intraocular pressure, ocular hypotensive eye drops are most commonly used. Unlike oral medications, patients’ knowledge on self-administration can lead to a great prognosis. As a result, good awareness, and support from healthcare professionals about eye drop instillation is crucial to lead a quality life in glaucoma patients.
Keywords: Glaucoma; Knowledge; Eye drop instillation